Analyzing Finite Dependent Clauses in English Writing: A Study of Mahlabatheng High School Grade 11 Students - Rethabile, Lekhooa D.; Motŝelisi, Lekena A. (Randwick International of Education and Linguistics Science Journal, 2024)
Though the concept of subordination has been explored in the context of L1 and L2 speakers of English language, more attention has been on the leaners of higher education. Against this background, the present paper set out to explore the use of finite dependent clauses by Mahlabatheng High School Grade 11 students where the main objective is to examine the extent to which the learners portray their ability to use finite dependent clauses and to also investigate whether they are able to use different types of such clauses. In order to achieve this objective, the study applied both qualitative and quantitative research methods, which included analysis of data obtained from students’ sample essays. The study used a combination of convenience and purposive sampling to select a sample of twenty-five students from whom the data was collected. The findings of the study revealed that students are able to demonstrate their ability to use the finite dependent clauses as on average, 96 percent of the total population were able to use finite dependent clauses in their writing and they used different types. The results further demonstrated that most students did not use the nominal clauses as compared to the other types of finite dependent clauses. The study, therefore, concludes that Mahlabatheng High School Grade 11 learners have ability to use finite dependent clauses. However, the recommendation is that more focus should be put on the nominal clauses.